PERIL AND PLEASURE: AN RDOC‐INSPIRED EXAMINATION OF THREAT RESPONSES AND REWARD PROCESSING IN ANXIETY AND DEPRESSION. Issue 3 (21st October 2013) - Dillon, Daniel G.; Rosso, Isabelle M.; Pechtel, Pia; Killgore, William D. S.; Rauch, Scott L.; Pizzagalli, Diego A.
<x xml:space="preserve">Abstract</x> As a step toward addressing limitations in the current psychiatric diagnostic system, the National Institute of Mental Health recently developed the Research Domain Criteria (RDoC) to stimulate integrative research—spanning self‐report, behavior, neural circuitry, and molecular/genetic mechanisms—on core psychological processes implicated in mental illness. Here, we use the RDoC conceptualization to review research on threat responses, reward processing, and their interaction. The first section of the manuscript highlights the pivotal role of exaggerated threat responses—mediated by circuits connecting the frontal cortex, amygdala, and midbrain—in anxiety, and reviews data indicating that genotypic variation in the serotonin system is associated with hyperactivity in this circuitry, which elevates the risk for anxiety and mood disorders. In the second section, we describe mounting evidence linking anhedonic behavior to deficits in psychological functions that rely heavily on dopamine signaling, especially cost/benefit decision making and reward learning. The third section covers recent studies that document negative effects of acute threats and chronic stress on reward responses in humans. The mechanisms underlying such effects are unclear, but the fourth section reviews new optogenetic data in rodents indicating that GABAergic inhibition of midbrain dopamine neurons, driven by activation of the habenula, may play a fundamental role in stress‐induced anhedonia. In addition to its basic scientific value, a better understanding of interactions between the neural systems that mediate threat and reward responses may offer relief from the burdensome condition of anxious depression.